2017
DOI: 10.1002/wcs.1438
|View full text |Cite
|
Sign up to set email alerts
|

‘Form is easy, meaning is hard’ revisited: (re) characterizing the strengths and weaknesses of language in children with autism spectrum disorder

Abstract: Children with autism spectrum disorder (ASD) demonstrate impairments in social interaction and communication, and in repetitive/stereotypical behaviors. The degree to which children with ASD also manifest impairments in structural language-such as lexicon and grammar-is currently quite controversial. We reframe this controversy in terms of Naigles' (Naigles, Cognition 2002, 86: 157-199) 'form is easy, meaning is hard' thesis, and propose that the social difficulties of children with ASD will lead the meaning-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 93 publications
7
71
0
Order By: Relevance
“…ysmenorrhea is one of the most prevalent gynecological problems among women [1]. The prevalence of dysmenorrhea is between 20% and 90% in various populations [2]. This wide variation could be related to the ethnic, sociocultural [3], or biological factors [4] or various definitions of dysmenorrhea in the previous studies.…”
Section: Introductionmentioning
confidence: 94%
“…ysmenorrhea is one of the most prevalent gynecological problems among women [1]. The prevalence of dysmenorrhea is between 20% and 90% in various populations [2]. This wide variation could be related to the ethnic, sociocultural [3], or biological factors [4] or various definitions of dysmenorrhea in the previous studies.…”
Section: Introductionmentioning
confidence: 94%
“…Generally, the obtained results from previous studies were categorized into three groups. The first group of studies indicated that the grammar development and the grammatical characteristics of children with ASD were similar to the TD children and their problems caused by pragmatic impairments and organization deficiencies in lexical/ semantic areas [6].…”
Section: Comparing Grammatical Characteristics Between Children With mentioning
confidence: 99%
“…It seems that the language of children with ASD is not abstract because they use language structures in a particular context or item, and there is no creativity in their spontaneous speech [9]. Naigles and Tek [6] examined whether children with ASD could learn the meanings of new verbs through the SB process. The results showed that the ASD group used the SB process like TD children.…”
Section: The Hypothesis Of Deficiency In the Syntactic Bootstrappingmentioning
confidence: 99%
“…Vocabulary can be further divided into vocabulary breadth (i.e., the number of items in the lexicon) and vocabulary depth (i.e., the richness of the semantic representation) [Ouellette, ; Ouellette & Beers, ]. Vocabulary breadth is stronger than vocabulary depth in children with ASD [McGregor et al, ], and poor “deep” semantic knowledge may be particularly important for understanding language impairments in ASD [Naigles & Tek, ]. Therefore, separately measuring the role of vocabulary breadth and depth may be more pertinent and meaningful for understanding reading comprehension deficits in children with ASD.…”
Section: Reading Comprehension In Asdmentioning
confidence: 99%